Experimental assessment of local void fraction and flow development in a U-bend piping system for air-water two-phase flow - Kukrer, Ergin; Eskin, Nurdil (Pergamon-Elsevier Science Ltd, 2023)
This paper presents an experimental investigation of air-water flow in a complete piping system, covering the two-phase flow development in injector, upstream, U-bend and downstream sections separately. Local void fractions and bubble numbers were measured with a dual optical probe. Two-phase flow conditions were established through a 40 mm diameter pipe with 180 l/min water and 30, 35 and 40 l/min air flow rates by the designed circular injector. In the horizontal upstream section, where a transition from bubbly to plug flow with elongated Taylor bubbles was observed, the fully-developed flow is reached at 37.5D. The average void fraction in the upstream region was acquired as 9.2%, 11.5% and 13.4%. The effect of two vertical 90-degree and one vertical 180-degree elbows is assessed in the U-bend section. While bubble break-up and locally annular flow were observed in the vertical upward section; bubble coalescence and accumulation resulting in higher average void fractions (30.8%, 33.8%, and 35.6%) were present in the downward section due to body forces and interphase interactions. After the bend section, disturbances were detected in the gas phase due to the increased water velocity and centripetal forces. Accordingly, a local transition to temporary churn flow is observed in the earlier downstream sections. The experimental assessment in our study shows that the system should be considered and analyzed as a whole to determine local transitions and differences in the flow regimes due to singularities in geometry.
Keywords: Air-Water Two-Phase Flow; Pipeline; U-Bend; Dual Optical Probe; Local Void Fraction; Gas-Liquid 2-Phase; Frictional Pressure-Drop; Heat-Transfer; Velocity; Pipe; Identification; Patterns; Behavior; Phases